Development of virtual control panel for single spindle configuration 2-axis filament winding machine(SSFWM) - Vicneswaran, Kuppusamy (2009)
This project is focused on developing the virtual control panel for single spindle configuration 2-axis filament winding machine (SSFWM) using Visual Basic 6.0. The software will interface with MMDS-RTD module Alpha version developed under the RDU070330 research project in Faculty of Electrical & Electronics Engineering, UMP. The MMDS-RTD module Alpha version which is capable of drive DC motor and Stepper motor only. In the software system, algorithms are designed to perform calculation for mathematical equation of fiber density, fiber width and product to calculate the optimal machine configuration such as number of running, velocities rotation of mandrel, velocities of carriage moment and angle of rotation. With this software system, user only need to enter the value of fiber density, diameter of mandrel, winding angle then the system will show the output their need and automatically send command to MMDS-RTD module Alpha version and control the filament winding machine. Furthermore the main idea is to transfer a fiber mould parameter equation into visual basic programming code. And from the programming code control the actuators on filament winding machine to meet with the setting given by user. This control panel capability control the movement of filament winding machine according to input parameter insert by user. Finally; the process is run continuously until the mandrel surface was fully covered by the composites.